In vitro analysis of Aegle marmelos leaf extracts on skin pathogens - Garima Mathur, Nidhija Roy, Ashwani Mathur (Journal of Applied Pharmaceutical Science, 2013)
The study was undertaken to screen various solvent and aqueous extracts of Aegle marmelos leaves display potent in vitro antioxidant activity, total phenolics and antimicrobial potential on various skin pathogens in order to explore the potential for future novel antioxidants in food and pharmaceutical formulations and antimicrobial agents. Four extracts showed varying degree of efficacy in each assay. Aqueous extract (486 mg GAE/g dry weight) exhibited the highest total phenolics content followed by methanol which was correlated with total antioxidant activity. Aqueous extract was more effective against S. saprophyticus, S. epidermidis, M.luteus in comparison to other extracts.
Keywords: Aegle marmelos, antioxidant, phenolics, antimicrobial, reactive oxygen species.